Hierarchical Model of Individual Consciousness - I. L. Prakopchyk-Haiko (Наука и техника)
The paper shows an invariant hierarchical model of individual consciousness. Each level of consciousness has a corresponding thinking with its specific features. The author defines development of individual consciousness as an expansion of its range.